( x -3 )² = y - 4
y = ( x - 3 )² + 4
One solution is located at the vertex: ( 3, 4 ).
y = - x + b
4 = - 3 + b
b = 7
( x - 3 )² = - x + 7 - 4
x² - 6 x + 9 = - x + 3
x² - 5 x + 6 = 0
x² - 2 x - 3 x + 6 = 0
x ( x - 2 ) - 3 ( x - 2 ) = 0
( x - 2 ) ( x - 3 ) = 0
x 1 = 2, x 2 = 3
y 1 = 5, y 2 = 4.
In order for this solution to be reasonable, the 2nd equation must be:
y = - x + 7
It would be 4 kg. Explanation: Bc each kg is .5 when rounded so u take .5 and multiply it by 8lbs
7+x is the awnser
unless you meant to type “A number is more than 7” then it would be x>7
Solve simultaneously.
4x - y = 8
6x + y = 2
Multiply top equation by 6, and bottom equation by 4, to eliminate x, so that we can find y.
~
24x - 6y = 48
24x - 4y = 8
Subtract top from bottom to form one equation.
~
-2y = 40
Therefore y is 20.
Put y back in to an equation, such as 4x - y = 8.
~
4x - 20 = 8
4x = 28
x = 7